Deposition of Suspended Clay to Open and Sand‐Filled Framework Gravel Beds in a Laboratory Flume. Issue 1 (23rd January 2018) - Mooneyham, Christian; Strom, Kyle
Abstract: Pulses of fine sediment composed of sand, silt, and clay can be introduced to gravel bed rivers through runoff from burn‐impacted hillslopes, landslides, bank failure, or the introduction of reservoir sediment as a result of sluicing or dam decommissioning. Here we present a study aimed at quantifying exchange between suspensions of clay and gravel beds. The questions that motivate the work are: how do bed roughness and pore space characteristics, shear velocity ( u ∗ ), and initial concentration ( C 0 ) affect clay deposition on or within gravel beds? Where does deposition within these beds occur, and can deposited clay be resuspended while the gravel is immobile? We examine these questions in a laboratory flume using acrylic, open‐framework gravel, and armored sand‐gravel beds under conditions of varying u ∗ and C 0 . Deposition of clay occurred to all beds (even with Rouse numbers ∼ 0.01). We attribute deposition under full suspension conditions to be an outcome of localized protected zones where clay can settle and available pore space in the bed. For smooth wall cases, protection came from the viscous wall region and the development of bed forms; for the rough beds, protection came from separation zones and low‐velocity pore spaces. Bed porosity was the strongest influencer of nondimensional deposition rate; deposition increased with porosity. Deposition was inversely related to u ∗ for the acrylic bed runs; no influence of u ∗ was found for the porous bed runs. Increases in discharge resulted in resuspension of clay from acrylic beds; no resuspension was observed in the porous bed runs. Key Points: Suspended clay deposited to both the surface and substrate of gravel beds even though Rouse numbers were on the order of 0.01 Scaled deposition rate was a function of the surface roughness characteristics and substrate porosity, but not shear velocity Little to no deposited clay was reentrained without mobilizing the surface layer due to sheltering, pore space accommodation, and cohesion